2019
DOI: 10.1002/jum.15065
|View full text |Cite
|
Sign up to set email alerts
|

Value of Computer Software for Assisting Sonographers in the Diagnosis of Thyroid Imaging Reporting and Data System Grade 3 and 4 Thyroid Space‐Occupying Lesions

Abstract: Objectives-To analyze the ability of thyroid ultrasound computer-aided diagnosis (CAD) detection software (AmCAD-UT; AmCAD BioMed Corporation, Taipei, Taiwan) to assist sonographers in diagnosing Thyroid Imaging Reporting and Data System grade 3 and 4 space-occupying lesions and to provide evidence for ultrasound doctors (UDs) to use the diagnostic recommendations of the AmCAD system to inform clinical decisions.Methods-In group 1, a retrospective study was performed on 234 cases of thyroid lesions confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…AmCAD-UT, a Food and Drug Administration (FDA)-approved CAD software device, is utilized to not only differentiate benign and malignant nodules, but also diagnose the features of thyroid nodules with different thyroid imaging reporting and data system (TI-RADS) [15]. Previous studies have shown that AmCAD-UT system has comparable performance to physicians in terms of diagnostic efficiency [13,[15][16][17]. However, there are few no detailed reports focused on diagnostic efficacy of nodule size using AmCAD-UT system.…”
Section: Introductionmentioning
confidence: 99%
“…AmCAD-UT, a Food and Drug Administration (FDA)-approved CAD software device, is utilized to not only differentiate benign and malignant nodules, but also diagnose the features of thyroid nodules with different thyroid imaging reporting and data system (TI-RADS) [15]. Previous studies have shown that AmCAD-UT system has comparable performance to physicians in terms of diagnostic efficiency [13,[15][16][17]. However, there are few no detailed reports focused on diagnostic efficacy of nodule size using AmCAD-UT system.…”
Section: Introductionmentioning
confidence: 99%
“…The system of AI ultrasonic intelligent auxiliary diagnosis, on the foundation of the static ultrasonic images, could quickly and conveniently automatically recognize and outline nodules and discriminate between benign and malignant nodules (13)(14)(15). Lu et al (23) retrospectively studied 234 thyroid nodules that had been confirmed by surgery and pathology. In their study, the AmCAD-UT system was used to analyze preoperative ultrasound images of nodules and was found to have a diagnostic sensitivity, specificity, and accuracy of 89.0%, 82.5%, and 86.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high diagnostic accuracy of this model, only 26% of the population (level 4) required additional biomarker testing. Similar to this, a commercially available AI tool has prospectively proved its capacity to assess malignancy risk in thyroid lesion assessment using ultrasonography, preventing needless biopsies (level 4) (47).…”
Section: Personalized Diagnosismentioning
confidence: 94%